PENGARUH PROFESIONALISME KERJA TERHADAP KINERJA KERJA PADA DINAS KOPERASI DAN UKM KOTA MEDAN - Reza Nurul Ichsan, Lukman Nasution (JURNAL PENELITIAN PENDIDIKAN SOSIAL HUMANIORA, 2022)
This study aims to find out how the influence of work professionalism on work performance at the Medan City Cooperatives and SMEs Office. This research uses quantitative methods. The population in this study was employees of the Medan City Cooperatives and SMEs Office, which amounted to 47 employees. The analysis technique used is a simple linear regression analysis technique. Based on the results of the study, there is an influence between work professionalism on work performance in the Medan City Cooperatives and SMEs Office. It is characterized by a count = 2.234 and a sig value of 0.0049. Thus, it can be concluded that the calculation of the ttabel ≥ is 2,234 ≥ 2,000.